The Effect of Substitute Good Price on the Volume of Indonesian Refined Palm Oil (RPO) Exports to Pakistan 2014-2021 - Rachel Nadine Saragih; Ni Ketut Budiningsih; Anak Agung Bagus Putu Widanta (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
The aim of this research is to estimate the effect of the international price of soybean oil, as a substitute good for palm oil, including Refined Palm Oil (RPO) on the volume of the Indonesian RPO exports to Pakistan. Using monthly data from 2014 to 2021, the variables were analyzed with multiple linear regression and the Error Correction Model (ECM). The finding reveals that the international price of soybean oil has a positive and significant effect on the volume of Indonesian RPO exports only in the long run. The research also estimates the effect of the export price of RPO, the exchange rate (Rupiah to US dollar), and Pakistan inflation on the volume of Indonesian RPO exports to Pakistan. The result shows that the export price of RPO has a negative and significant effect on the volume of RPO exports in the long run and in the short run, the exchange rate and Pakistan inflation are statistically insignificant to affect the volume of Indonesian RPO exports. In conclusion, it is suggested that monitoring on the behavior of international prices of soybean oil, as a substitute good for palm oil, should be done on a regular basis; all palm oil stakeholders should collaborate effectively to ensure that the export price of Indonesian RPO remains competitive. The Government of Indonesia should consider to continue negotiating with the Government of Pakistan on the possibility of reducing palm oil import tariffs more than previously agreed in the scheme of the Indonesia-Pakistan Preferential Trade Agreement (IP-PTA) of 2012.